(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper the components of concrete structure, which are steel and concrete, and corrosion will be discussed. Followed by a description of the old technique that was used to strength and repair reinforced concrete structures. Then this essay presents a state-of-the-art technique that is fiber reinforced polymer and reviews of its manufacturing methods. Next, the positive and negative aspects of using fiber reinforced polymer sheets as increase shear and flexure capacity will be analyzed. Finally, a brief summary will be concluded.